A critical narrative analysis of the deployment of corporate arrangements in the conduct of government employee pension fund - Kekana, Makabelo Ephraim (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPA (Public Management and Planning))--University of Stellenbosch, 2010.